Penerapan Penyusunan Laporan Keuangan Yayasan Berdasarkan PSAK 45 - Anand, Dev (Jurnal Kajian Akuntansi, 2018)
AbstractNonprofit organizations in Indonesia today have not prioritized financial management systems in accordance with applicable standards, but still tend to emphasize the quality of program priorities. Whereas the financial statements which are the result of the financial management system are the tools of accountability for the management of resources managed by management, and are used as a means of controlling and evaluating managerial and organizational performance. The purpose of this study is to apply financial accounting standards for non-profit organizations in Indonesia based on Statement of Financial Accounting Standards (PSAK) No. 45. This research uses descriptive - qualitative method, which is a method that is carried out by collecting data, and analyzing data to get a clear picture of the problems or phenomenon. The data collection techniques in this study are field surveys, unstructured interviews and literature studies. This study provides solutions, recommendations and directions for the preparation of the Financial Report of the Hajjah Roestilah Foundation, so this study will create a new shape of Hajjah Roestilah's Financial Statements that are in accordance with the provisions stipulated in the Statement of Financial Accounting Standards (PSAK) No. 45. The expected final result of this study is a new financial statements that can be used as an accurate source of information for decision makers.Keywords: Non-profit organization, PSAK No. 45, financial statements, accountability AbstrakOrganisasi nirlaba di Indonesia dewasa ini belum memprioritaskan sistem pengelolaan keuangan sesuai dengan standar yang berlaku,namun masih mengedepankan terhadap prioritas keunggulan program yang dijalankan. Padahal laporan keuangan yang merupakan hasil dari sistem pengelolaan keuangan merupakan alat pertanggungjawaban atas pengelolaan sumber daya yang dikelola oleh manajemen, dan digunakan sebagai alat pengendali serta sebagai alat evaluasi kinerja manajerial dan organisasi. Tujuan dari penelitian ini adalah untukmenerapkan standar akuntansi keuangan yang berlaku pada organisasi nirlaba sejalan dengan PSAK No. 45. Penelitian menggunakan metode deskriptif kualitatif yaitu metode yang dilakukan dengan cara mengumpulkan data-data, serta menganalisa data yang nantinya akan memperoleh kejelasan mengenai permasalah yang diteliti. Tehnik pengumpulan data dalam penelitian ini menggunakan survei lapangan,wawancara tidak tersruktur dan studi kepustakaan. Penelitian ini memberikan solusi, rekomendasi serta arahan terhadap  penyusunan Laporan Keuangan Yayasan Hajjah Roestilah, agar Laporan Keuangan tersebut sesuai dengan ketentuan yang tertuang di PSAK No. 45, sehingga Laporan keuangan tersebut dapat digunakan sebagai sumber informasi yang akurat bagi para pengambil keputusan.Kata kunci: Organisasi nirlaba, PSAK No. 45, laporan keuangan, pertanggungjawaban